The consequences of open defecation on Kakungu, Kassena-Nankana West District, Ghana - Ayonno, Martha Lardi (University of Cape Coast, 2020)
The study seeks to describe the consequence of open defecation on Kakungu due to lack of household latrines in the Kassena-Nankana West District in Ghana. The study employed both qualitative and quantitative Methodology in data collection. A questionnaire administration to three hundred households randomly selected from two section of the community. Non-probability-accidental sampling strategy was administered to 300 responded out of 665 residences from Kakungu community in the District. Findings from the study revealed that some respondents had no toilet facility in their home. Those who had the facility were under construction due to malfunctioning. Those who had not patronize public toilets with a cost between one Ghana cedi per trip. Those who could not afford practice open defecation. Forty-five (45) persons which stands for 15% also think that washing your hands immediately before eating is very good hygienic practice. The remaining one hundred and twenty-nine (129) respondents think that hands should be washed anytime hands are dirty or better still anytime we do something that contaminates the hand. The researcher concluded that, the inability of most inhabitants of Kakungu community to accessed, afford, maintained toilet facility and wash their hands at all critical times highly influence the seasonal cases of cholera in the community as shown above. As a result, of this research, I therefore recommend, the adoption Community-Led Total Sanitation (CLTS) approach to increase access to sanitation and hygiene services in Kakungu, the International Development Agency through community water and sanitation Agency in collaboration with the ministry of sanitation and water resource should support the people of Kakungu community with the digni-loo type of toilet to improve access to sanitation facility. Description:
ix, 66p:,ill.
Keywords: Open defecation; Kakungu; Sanitation